2013
DOI: 10.1364/oe.21.021596
|View full text |Cite
|
Sign up to set email alerts
|

Optical temperature sensing of NaYbF_4: Tm^3+ @ SiO_2 core-shell micro-particles induced by infrared excitation

Abstract: NaYbF(4):Tm3+@SiO(2) core-shell micro-particles were synthesized by a hydrothermal method and subsequent ultrasonic coating process. Optical temperature sensing has been observed in NaYbF4: Tm(3+)@SiO(2)core-shell micro-particles with a 980 nm infrared laser as excitation source.The fluorescence intensity ratios, optical temperature sensitivity, and temperature dependent population re-distribution ability from the thermally coupled (1)D(2)/(1)G(4) and (3)F(2) /(3)H(4) levels of the Tm(3+) ion have been analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
54
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(57 citation statements)
references
References 31 publications
3
54
0
Order By: Relevance
“…(1) and the values of coefficient and energy gap were found to be $ 6.67 and 706.68 cm À 1 , respectively. For optical thermometry applications, the sensing sensitivity was estimated from the equation of S ¼ dR/dT ¼ R(ΔE 12 /kT 2 ) [23,24]. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…(1) and the values of coefficient and energy gap were found to be $ 6.67 and 706.68 cm À 1 , respectively. For optical thermometry applications, the sensing sensitivity was estimated from the equation of S ¼ dR/dT ¼ R(ΔE 12 /kT 2 ) [23,24]. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Optical thermometry used a line shift technique was first reported in Y 2 O 2 S:Eu phosphor by Kusama et al [1]. From then on, optical temperature sensing was widely studied in the CdSe and CdTe semiconducting quantum dots, organic phosphors, rare earth ion-doped oxide bulks, fluoride nanoparticles, and glass ceramics containing fluoride nanocrystals [2][3][4][5][6][7][8][9]. Among the materials used for optical thermometry, quantum dots nano-crystals, fluoride nano-crystals, and organic compounds are easy to be oxidized at high temperature, and only available in low-temperature range.…”
Section: Introductionmentioning
confidence: 99%
“…Dong et al revealed that the optical temperature sensor, which was based on the UC emission of Er-Mo doped Yb 3 Al 5 O 12 , can be operated in the temperature range of 293-973 K with a maximum sensitivity of 0.0048 K À1 [11]. Noticeably, the optical temperature sensing studies are mainly focused on glasses and fluorides [12][13][14]. However, they have some drawbacks.…”
Section: Introductionmentioning
confidence: 99%